2014
DOI: 10.1212/wnl.0000000000000154
|View full text |Cite
|
Sign up to set email alerts
|

APOE ε4 worsens hippocampal CA1 apical neuropil atrophy and episodic memory

Abstract: Objectives: Using high-resolution structural MRI, we endeavored to study the relationships among APOE e4, hippocampal subfield and stratal anatomy, and episodic memory.Methods: Using a cross-sectional design, we studied 11 patients with Alzheimer disease dementia, 14 patients with amnestic mild cognitive impairment, and 14 age-matched healthy controls with no group differences in APOE e4 carrier status. Each subject underwent ultra-high-field 7.0-tesla MRI targeted to the hippocampus and neuropsychological ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 34 publications
8
53
1
Order By: Relevance
“…Contrastingly, strong correlations were also described in AD patients between delayed recall performance and the widths of CA1-SRLM and CA1-SP, while DG/CA3 size did not significantly correlate with any aspect of memory performance (Kerchner et al, 2012). In a larger and mixed group (controls, MCI and AD patients), Kerchner et al (2014) replicated their first finding of a CA1-SRLM to delayed recall association.…”
Section: Cognitive Correlates Of Subfield Atrophy In Aging and Dementiamentioning
confidence: 72%
See 2 more Smart Citations
“…Contrastingly, strong correlations were also described in AD patients between delayed recall performance and the widths of CA1-SRLM and CA1-SP, while DG/CA3 size did not significantly correlate with any aspect of memory performance (Kerchner et al, 2012). In a larger and mixed group (controls, MCI and AD patients), Kerchner et al (2014) replicated their first finding of a CA1-SRLM to delayed recall association.…”
Section: Cognitive Correlates Of Subfield Atrophy In Aging and Dementiamentioning
confidence: 72%
“…In a longitudinal study of subfield thickness over two years, the same authors showed a stronger rate of atrophy in the subiculum (Donix et al, 2010b). By contrast, Kerchner et al (2014) found a selective, dose dependent effect on the CA1-SRLM width (yet, controls were pooled with MCI and demented patients in this analysis), while Mueller et al reported a detrimental effect of the ε4 allele on CA3/DG volume in healthy elderly, but not in middle aged individuals (Mueller and Weiner, 2009;Mueller et al, 2008). Overall, the important variability in these results makes it difficult to get a clear picture of the preferential effect of APOE4 on hippocampal subfield volume in asymptomatic individuals.…”
Section: Cognitively Intact Individuals At Risk For Admentioning
confidence: 93%
See 1 more Smart Citation
“…For example, many studies have shown that the APOE ε4 gene affects the hippocampal subfields and cortical thickness in AD and MCI [23, 24]. APOE ε4 allele carriers have shown smaller hippocampal subfields [15, 25, 26] and cortical thickness [24, 27]. The APOE ε4 genotype can modify the correlation between cognitive status and metabolites from the hippocampus [28].…”
Section: Introductionmentioning
confidence: 99%
“…These techniques were applied to a variety of diseases in small single-site studies and usually found subfield volumetry to be superior to standard whole hippocampal volumetry for the detection of hippocampal damage in the early stages of the disease process, for differentiating between diseases or for the investigation of structure/function relationships (e.g., Wang et al, 2006;Ballmaier et al, 2008;Mueller et al, 2008;Schobel et al, 2009;Neylan et al, 2010;Bender et al, 2013;Kerchner et al, 2014;SchoeneBake et al, 2014;Chao et al, 2014;Hsu et al, 2015;De Flores et al, 2015;Pluta et al, 2012;Yushkevich et al, 2015b). The promise of hippocampal subfield volumetry techniques however led to two unexpected developments that could potentially limit the usefulness of this approach.…”
Section: Introductionmentioning
confidence: 99%